The Low FODMAP Diet in Irritable Bowel Syndrome: Current State of Knowledge and Therapeutic Perspectives - Solarz, Monika Barbara; Piekarska, Julia; Solarz, Justyna Maria; Wawrzyńców, Jakub Tomasz; Cyrkler, Weronika; Robak, Jakub; Telega, Stanisław; Bollin, Paweł; Szymczak, Urszula; Lachór, Wojciech Wiesław (Quality in Sport, 2025)
Irritable bowel syndrome (IBS) is a chronic functional gastrointestinal disorder that significantly reduces patients’ quality of life. One of the primary therapeutic approaches is the low FODMAP diet, which involves the restriction of fermentable oligo-, di-, monosaccharides, and polyols. The aim of this review is to summarize the current knowledge regarding the effectiveness of this diet in alleviating IBS symptoms, its impact on the gut microbiota, and its long-term health consequences. Research findings confirm that the low FODMAP diet effectively reduces symptoms, particularly in patients with diarrhea-predominant IBS (IBS-D), although long-term adherence may lead to a reduction in beneficial gut bacteria. Adherence challenges and the lack of clear guidelines on FODMAP reintroduction represent significant clinical issues. Alternative strategies, such as the Mediterranean diet, may help mitigate the negative effects of FODMAP elimination. The low FODMAP diet also shows potential in children and patients with inflammatory bowel disease (IBD), although further studies are needed. In the future, it will be essential to develop support strategies for patients and to personalize dietary recommendations, which may contribute to sustained improvements in the quality of life for individuals with IBS.